3-Oxo-5-(piperidin-1-yl)-2,3-dihydro-1H-pyrazole-4-carbonitrile - Al-Adiwish, Wedad M.; Wan Ahmad, Wan Yaacob; Adan, Dalina; Mohamed Tahir, Mohamed Ibrahim; Kassim, Mohammad (International Union of Crystallography, 2011)
In the title compound, C9H12N4O, the piperidine ring adopts a chair conformation and makes a dihedral angle of 42.49 (11)° with the approximately planar pyrazole moiety [maximum deviation = 0.038 (2) Å]. In the crystal, N—H(...)O and N—H(...)N hydrogen bonds and a weak C—H(...)O interaction link the molecules into sheets lying parallel to (110).